Changes in classical kinematics and non‐linear parameters after a maximal 100‐m front‐crawl bout - Barbosa, Tiago M. (2017)
In a linear system there is proportionality between input and output. Under this framework it is expected that the amount of change in sports performance must be proportional to variations in the inputs.